2020
DOI: 10.1016/j.ijso.2020.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and associated factors of emergence agitation after general anesthesia and surgery among pediatric patients: A prospective follow-up study

Abstract: Introduction: Emergence agitation is one of the significant anesthetic and surgery-related complications. It is usually short-lived but causes self-injury during agitation and it led to parental anxiety. This study was aimed to assess incidence and factors associated with emergence agitation after general anesthesia and surgery among pediatric patients at University of Gondar specialized hospital. Methods: A prospective follow-up study conducted on 153 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In pediatric patients undergoing surgery, delirium rates can reach up to 66% [ 2 , 12 ]. Previous studies have indicated higher rates of recovery agitation following ophthalmic and ear, nose, and throat surgeries, suggesting the significance of these procedures as determinants of delirium [ 13 ]. Eshetie et al [ 13 ] reported a higher incidence of delirium in ophthalmic and ear-nose-throat surgeries (56.2%) compared to other surgical procedures (32.7%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pediatric patients undergoing surgery, delirium rates can reach up to 66% [ 2 , 12 ]. Previous studies have indicated higher rates of recovery agitation following ophthalmic and ear, nose, and throat surgeries, suggesting the significance of these procedures as determinants of delirium [ 13 ]. Eshetie et al [ 13 ] reported a higher incidence of delirium in ophthalmic and ear-nose-throat surgeries (56.2%) compared to other surgical procedures (32.7%).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated higher rates of recovery agitation following ophthalmic and ear, nose, and throat surgeries, suggesting the significance of these procedures as determinants of delirium [ 13 ]. Eshetie et al [ 13 ] reported a higher incidence of delirium in ophthalmic and ear-nose-throat surgeries (56.2%) compared to other surgical procedures (32.7%). Ophthalmic surgeries, in particular, have a higher incidence of postoperative delirium due to changes in vision following the operation compared to other pediatric surgeries [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As might be expected, EA is also associated with parental and staff dissatisfaction 2 . EA has been associated with other complications like impaired functional recovery 3 . The exact mechanism of EA is still unknown despite identifying numerous risk factors.…”
Section: Introductionmentioning
confidence: 96%
“…2 EA has been associated with other complications like impaired functional recovery. 3 The exact mechanism of EA is still unknown despite identifying numerous risk factors. Potential risk factors for EA include patient age, temperament, preoperative anxiety, pain, type of surgery, and anesthetic strategy.…”
Section: Introductionmentioning
confidence: 99%